Hard talk, costly walk: The evolution of a soft budget constraint syndrome in a football club at the periphery of Europe - Bertheussen, Bernt Arne (Frontiers in Sports and Active Living, 2023)
A football club is exposed to a soft budget constraint (SBC) syndrome if it still survives after finding it impossible to break even financially in the long run. This in-depth case study presents a historical analysis of the evolution of an SBC syndrome in a top-tier Arctic football club over 30 years using public archive data. In oral speeches, strategy documents, and other official situations, the hierarchy at the club emphasized the importance of operating financially sustainable, that is, complying with a hard budget con¬straint approach (HBC). The club went along this path during the first years after entering the top tier in the mid-1980s. This was made possible by a team of low-cost local players. However, in line with increased media and sponsorship revenues in the 1990s, the economic threshold for competing at the top-level rose. Thus, during the last two decades of the club’s financial history, the budget constraint (BC) approach softened. Primarily, a distant benefactor and capital injections from a joint-stock company owned mainly by the local bank and local energy company funded the overspending. Furthermore, the study uncovers how a soft financial control and monitoring system introduced by the national football association failed to emancipate the club from the SBC syndrome. The study finally suggests some measures that can eventually harden the BC at this as well as many other financially struggling European football clubs.